PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASI Studi pada Guru di SMP Negeri Se-Kawedanan Tayu Kabupaten Pati - Rasilan, 11 52.02 0074 (Students Journal of Economic and Management, 2013)
The purpose of this study was to analyse, experimentally, the relationships between principal leadership and work motivation to teacher performance with organizational commitments as intervening variable. Participants compriseed 150 teachers having educational certificate from the whole Kawedanan Tayu Pati region. With characteristics: min 30 years old, min S1 degree, and work duration min 5 years. The results are the first hypothesis (H1) âPrincipal leadership has positive and significant effect on organizational commitment, it means the better principal leadership will increase organizational commitmentâ. The second hypothesis (H2) âWork motivation doesnât influence organizational commitment, it means the motivation given by teachers doesnât increase organizational commitmentâ. The third hypothesis (H3) âPrincipal leadership has positive and significant impact on teacher performance, it means the better principal leadership will increase teacher performanceâ. The fourth hypothesis (H4) âWork motivation has positive and significant on teacher performance, it means the better work motivation will increaseÂ teacher performanceâ. The fifth hypothesis (H5) âOrganizational commitment has positive and significant impact on teacher performance, it means the better organizational commitment will increase teacher performanceâ. Key words: Principal leadership, work motivation, organizational commitment, and teacher performance.